Nano-encapsulation of fish oil in nano-liposomes and its application in fortification of yogurt. (1st February 2017) - Ghorbanzade, Tahere; Jafari, Seid Mahdi; Akhavan, Sahar; Hadavi, Roxana
Highlights: Nano-encapsulated fish oil was produced successfully from liposomes. Nano-encapsulation resulted in a significant reduction in peroxide value. Yogurt with nano-encapsulated fish oil had a higher DHA and EPA content. Fortified yogurt gave closer results to control sample for sensory evaluation. Abstract: Fish oils have many dietary benefits, but due to their strong odors and rapid deterioration, their application in food formulations is limited. For these reasons, nano-liposome was used to nano-encapsulate fish oil in this study and encapsulated fish oil was utilized in fortifying yogurt. Physicochemical properties of produced yogurt including pH, acidity, syneresis, fatty acid composition, peroxide value as well as sensory tests were investigated during three weeks storage at 4 °C. Nano-liposome encapsulation resulted in a significant reduction in acidity, syneresis and peroxide value. The results of gas chromatography analyses revealed that after 21 days storage, yogurt fortified with nano-encapsulated fish oil had a higher DHA and EPA contents than yogurt containing free fish oil. Overall, the results of this study indicates that adding nano-encapsulated fish oil into yogurt gave closer characteristics to control sample in terms of sensory characteristics than yogurt fortified with free fish oil.